A competitive alphascreen assay for detection of hyaluronan. (29th December 2017) - Huang, Xiayun; Schmidt, Tannin A; Shortt, Claire; Arora, Shivani; Asari, Akira; Kirsch, Thorsten; Cowman, Mary K
Abstract: A method for specific quantification of hyaluronan (HA) concentration using AlphaScreen® (Amplified Luminescent Proximity Homogeneous Assay) technology is described. Two types of hydrogel-coated and chromophore-loaded latex nanobeads are employed. The proximity of the beads in solution is detected by excitation of the donor bead leading to the production of singlet oxygen, and chemiluminescence from the acceptor bead upon exposure to singlet oxygen. In the HA assay, the donor bead is modified with streptavidin, and binds biotin-labeled HA. The acceptor bead is modified with Ni(II), and is used to bind a specific recombinant HA-binding protein (such as HABP; aggrecan G1-IGD-G2) with a His-tag. Competitive inhibition of the HA–HABP interaction by free unlabeled HA in solution is used for quantification. The assay is specific for HA, and not dependent on HA molecular mass above the decasaccharide. HA can be quantified over a concentration range of approximately 30–1600 ng/mL using 2.5 μL of sample, for a detectable mass range of approximately 0.08–4 ng HA. This sensitivity of the AlphaScreen assay is greater than existing ELISA-like methods, due to the small volume requirements. HA can be detected in biological fluids using the AlphaScreen assay, after removal of bound proteins from HA and dilution or removal of other interfering proteins and lipids.